Nanostructured Photocatalysts Advanced Functional Materials - Yamashita, Hiromi; Li, Hexing; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
While books on semiconductor TiO2 photocatalysis are legion, nanostructured controlled photocatalysts are attractive beyond standard semiconductors, and this book is devoted to the many novel uses of advanced TiO2 and MOF-based photocatalysts. Details on synthesis, characterization, and reaction applications of nanostructured photocatalysts are summarized. Other new materials discussed in this book are Bi- W- oxides, metal complexes, and unique porous materials. This book contains methods of preparation and characterization of unique nanostructured photocatalysts, and details about their catalytic action. Contributors to this volume are leading Asian researchers in Photocatalysis. It will appeal to researchers wishing to know how to design new types of photocatalysts with controlled nanostructures.
Synthesis of novel titania and its photocatalytic activity -- Preparation of controllable crystalline titania and study on the photocatalytic properties -- Controllable synthesis and photocatalytic activities of TiO2 nanocrystals -- Nanostructured elemental photocatalysts: development and challenges -- Development of visible light responsive morphology controlled TiO2 photocatalyst -- Development of advanced nanoarchitectures for photocatalytic treatment of NOx: challenges and prospects -- Preparation of TiO2 nanotubes-based electrophotocatalysts and their application in organic pollutants oxidation -- Hollow core-shell titania photocatalysts for selective organic synthesis -- Design of film photocatalysts deposited on rotating disk for degradation of organic dyes in wastewater -- Photocatalyst prepared using ion beam -- F-doping on the photocatalytic activity and microstructures of nanocrystalline TiO2 Powders -- Photocatalytic decomposition of NH3 over Fe-doped TiO2 prepared by solid-state impregnation -- Surface-functionalized TiO2 photocatalyst -- Design of nanostructured thin film photocatalysts and their advanced functions -- Silica-supported TiO2 photocatalyst supported on hydrophobic modified silica support -- Photodegradation of aromatic pollutants in water over TiO2 supported on molecular sieves -- Layered double hydroxide photocatalysts for CO2 conversion in H2O -- Plasmonic photocatalysts -- Bismuth contaning complex oxides nano- and microstructures: shape control and associated visible‐light‐driven photocatalytic activities -- Synthesis and Facet-dependent photocatalytic activity of layered BiOCl -- Synthesis of square Bi2WO6 nanoplates as high-activity visible-light-driven photocatalysts -- Formation of novel BiOCl/Bi2O3 and WO3/BiOCl/Bi2O3 for efficient visible-light photocatalysis -- Visible light responsive photocatalysts and photoelectrodes using WO3 semiconductor for degradation of various organic compounds and water splitting -- Z-scheme semiconductor photocatalyticsystems -- Silica-supported metal complex photocatalyst -- Metal-organic-framework (MOF) and porous-coordination-polymer (PCP) based photocatalyst -- Photocatalytic CO2 reduction to CO by ZIF-9/TiO2 -- Nanometal loaded metal-organic-framework photocatalysts. .
Keywords: Nanochemistry; Catalysis; Energy harvesting; Environmental chemistry; Chemistry, Technical; Inorganic chemistry; Nanochemistry; Catalysis; Energy Harvesting; Environmental Chemistry; Industrial Chemistry; Inorganic Chemistry